Formulation of Menthol-Loaded Nanostructured Lipid Carriers to Enhance Its Antimicrobial Activity for Food Preservation - Parizad Piran; Hossein Samadi Kafil; Saeed Ghanbarzadeh; Rezvan Safdari; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2017)
Purpose: Due to the antimicrobial property, menthol have significant potential for food preservation and foodstuff shelf life improvement. Nevertheless, menthol instability, insolubility, and rapid crystallization in aqueous media make it unsuitable for used in food products. This work was aimed to prepare menthol-loaded nanostructured lipid carriers (NLCs) to enhance its antimicrobial activity. Methods: Morphology, particle size and size distribution, encapsulation efficiency percent (EE%), and physical stability of the optimized formulation, prepared by hot melt homogenization method, were characterized by scanning electron microscopy, particle size analyzing, gas chromatography, and X-ray diffraction (XRD) methods. Minimum inhibitory concentration and minimum bactericidal concentration of menthol-loaded NLCs were evaluated and compared with conventional menthol emulsion against various Gram-positive (Staphylococcus aureus, Bacillus cereus) and Gram-negative bacteria (Escherichia coli), as well as one fungus (Candida albicans). Results: Menthol-loaded NLCs were spherically shaped nanosized (115.6 nm) particles with narrow size distribution (PDI = 0.2), suitable menthol EE% (98.73%), and appropriate physical stability after 90 days of storage period. XRD results indicated that menthol was in the amorphous form in the nanoparticles matrix. Antibacterial assay results revealed that the menthol-loaded NLCs exhibited significantly higher in vitro antimicrobial property than conventional menthol emulsion. The results also indicated that menthol-loaded NLCs had better effect on fungi than bacteria, and furthermore, antibacterial efficiency on Gram-positive bacteria was higher than Gram-negative bacteria. Conclusion: In conclusion, NLCs could be a promising carrier for improvement of antimicrobial activity and preservation efficacy of essential oils in foodstuffs.